2020
DOI: 10.1111/jfpp.14444
|View full text |Cite
|
Sign up to set email alerts
|

Chemometrics characterization of volatile changes in processed bayberry juice versus intact fruit during storage by headspace solid‐phase micro‐extraction combined with GC–MS

Abstract: Chinese bayberry deteriorates rapidly after harvest. To gain a better understanding of flavor deterioration, we investigated the volatile changes in processed bayberry juice and intact fruits using HS–SPME/GC–MS during storage. The concentration of hexanal, which has a “grass” aroma, and other associated aldehydes significantly decreased (p < .05) during storage, and it is likely that these losses are responsible for the decrease in freshness. Ethanol (“alcoholic” note), ethyl acetate (“fruity” note), and acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Besides, in a study related to strawberry guava fruit, the hexanoic acid was specified to have an acrid acid (astringent) taste (Pino et al, 2001). And, indifferent a few studies on juices like bayberry, papaya, peach juices, the hexanoic acid was reported to be off-flavor for juice (Fang et al, 2020). Another important compound, benzaldehyde also has a bitter almond, burnt sugar, fruity, and cherry flavor (Pino et al, 2001), and it is not off-flavor.…”
Section: Ta B L Ementioning
confidence: 99%
“…Besides, in a study related to strawberry guava fruit, the hexanoic acid was specified to have an acrid acid (astringent) taste (Pino et al, 2001). And, indifferent a few studies on juices like bayberry, papaya, peach juices, the hexanoic acid was reported to be off-flavor for juice (Fang et al, 2020). Another important compound, benzaldehyde also has a bitter almond, burnt sugar, fruity, and cherry flavor (Pino et al, 2001), and it is not off-flavor.…”
Section: Ta B L Ementioning
confidence: 99%
“…Non-volatile compounds such as organic acids contribute to the taste, while volatile compounds confer the aroma. Gas chromatography–mass spectrometry (GC–MS) is a standard method for detecting and quantifying volatile compounds in the food industry ( Fang et al, 2020 ). Many studies have demonstrated the application of GC–MS in the analysis of plant-based fermentation products.…”
Section: Introductionmentioning
confidence: 99%
“…The high content of aldehydes and terpenes is one of the most important characteristics of the volatile components in bayberry. Specially, β-caryophyllene has been identified as the most dominant terpene compound and the key flavor component of bayberry in previous studies [ 1 , 16 , 18 , 19 ]. Our results show that β-caryophyllene was the most abundant volatile compound in IBW and was 3.73 times more abundant in IBW than in FBW.…”
Section: Resultsmentioning
confidence: 99%